TEACHING WORK INTENSIFICATION AND PSYCHOLOGICAL DETACHMENT FROM WORK: THE MEDIATING EFFECT OF ILLEGITIMATE TASKS AND WORK-FAMILY CONFLICT - Neves, Paula C.; Andrade, Cláudia (Seven Editora, 2025)
The intensification of work translates into an increase in workload and the assignment of new tasks of varying complexity and nature. Both the intensification of teaching work in general, and specifically the performance of tasks considered illegitimate (e.g. tasks asked of teachers that they perceive as unnecessary or unreasonable) are a source of stress for teachers with implications for their well-being, particularly in terms of increasing family conflict. On the other hand, the ability/possibility of recovering from work has been identified as an essential element not only for the effective performance of work tasks, but also for teachers' well-being.  Considering the scarcity of studies on this subject in the teaching profession, a quantitative study was carried out on a sample of 131 teachers with the aim of assessing the role of illegitimate tasks and work-family conflict in the relationship between work intensification and psychological detachment from work. The results of the study validated a dual influence model in which work intensification is associated with the performance of illegitimate tasks (unnecessary and unreasonable) and work-family conflict, which in turn negatively influences psychological detachment from work.DOI: https://doi.org/10.56238/sevened2025.033-001